ECONOMIC FOUNDATIONS FOR IMPROVING TARIFF POLICY IN THE TELECOMMUNICATIONS SERVICES MARKET (Multidisciplinary Journal of Science and Technology, 2026)
This study explores the economic foundations for improving tariff policy in the telecommunications services market. The research analyzes how changes in competitive conditions, cost structures, digital technology adoption, and evolving consumer demand influence tariff formation. The results aim to support the development of flexible, efficient, and sustainable pricing mechanisms that enhance market performance and ensure balanced interests of service providers and consumers.